Career Transition to the Professoriate: Midlife Women’s Process, Challenges, Supports, and Strategies - Catherine A. Cherrstrom (Adult Education Research Conference, 2015)
: The numbers of new faculty with prior careers and women faculty are increasing. However, traditional theories may not explain this intersection in examining faculty careers. The purpose of this study was to investigate the career transitions and strategies of women midlife career changers to the professoriate.
Keywords: career transition; career change; midlife; faculty; higher education